Arthur Conan Doyle and photography : traces, fairies and other apparitions - Stiegler, Bernd; Filkins, Peter (Edinburgh : Edinburgh University Press, 2023)
Arthur Conan Doyle is best known as the author of the Sherlock Holmes stories. However, his works are far more extensive than these familiar works. They include historical novels, political pamphlets, historical studies, science fiction novels and, last but not least, numerous publications on spiritualism. Photography plays a central role in his work and gives rise to a highly peculiar world of imagination. The photographs allow us to take a look at the world in around 1900 with all its oddities. For Conan Doyle's contemporaries, Sherlock Holmes was a real figure. To Conan Doyle, photographs of elves, the dead and ghosts testified to their existence. This book collects these images, along with the imaginarium that surrounds them.
1. Forays into the Wilderness: Conan Doyle as Amateur Photographer; 2. Sherlock Holmes: The Detective as Camera; Digression: The Sherlock Holmes Exhibit, 1951; 3. Photographs from the Heart of Darkness: The Congo Atrocities; 4. A Fairytale of Science: The Lost World; Digression: Arthur Conan Doyle and Harry Houdini; 5. Photos from the Shadowy Realm: Photography and Spiritualism; 6. Fairies and Gnomes: A Photographic Re-enchantment of the World; Epilogue: Strategic Realism; Notes; List of Illustrations; Acknowledgments; Index of Names.
Translated from the German.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 09, 2023).
Translated from the German.
JSTOR
Keywords: Doyle, Arthur Conan, -- 1859-1930; Doyle, Arthur Conan, -- 1859-1930; Spiritualism -- Great Britain -- History; Literature and photography -- Great Britain -- History; Spiritisme -- Grande-Bretagne -- Histoire; Littérature et photographie -- Grande-Bretagne -- Histoire; Literature and photography; Spiritualism; Great Britain; Literature: history & criticism; Literary studies: fiction, novelists & prose writers; Spirituality & religious experience; Literature; Electronic books; History